Representation in the production of English idioms by proficient Iranian EFL learners - Yeganehjoo, Masoomeh (2012)
A natural and native-like communication involves identification of and access to a vast body of idiomatic expressions in a language. These expressions are used effortlessly among native speakers, but their use has created many difficulties for second and foreign language learners. Studying how idiomatic expressions are represented in the EFL (English as foreign language) learners’ mental lexicon reflects difficulty EFL learners have in acquiring and using them. Ample research has investigated the representation and processes involved in idiom comprehension in L1 (first language) contexts, but only limited studies have explored the production of idiomatic expressions in an EFL context. Therefore, this study aimed to investigate: firstly how English idiomatic expressions are represented in and accessed from the proficient EFL learner’s mental lexicon during the course of speech production, and secondly, the impact of idiom decomposability and cross linguistic similarities on idiom representation and production in an EFL context. Three cross-modal priming experiments were conducted to investigate the research questions of the study. In the first experiment, the assumptions of the superlemma theory, i.e., the unitary and compositional representations of English idioms in EFL speech production were examined by measuring the response latencies of 31 adult proficient Iranian EFL learners during the production of English idioms. The second experiment investigated the influence of idiom decomposability on representation and production of English idioms in a different group of 30 competent Iranian EFL learners. Another group of 27 proficient Iranian EFL learners participated in the third experiment to explore how or whether cross-linguistic similarities affect the representation of English idiomatic expressions during speech production. Three different lists of idioms were selected to correspond to each research question of the study in particular. The participants had to recall a previously memorized list of items using a cue (a visual prompt). Audio prime words were employed simultaneously to observe the unconscious effect of the variables of the study on the EFL learners’ response latencies (reaction times) when producing the phrases. The results of these experiments support firstly, the hybrid representation of idiomatic expressions in the EFL learners’ mental lexicon that is idioms have their own lexical entry which links to the simple lemmas composing the idiom; hence, faster production of English idioms compared to their literal counterpart phrases was observed by the proficient Iranian EFL learners. Secondly, the findings suggest that the nondecomposable idioms have the benefit of being produced faster compared to the decomposable idioms due to the higher activation of their unitary representation in the EFL learners’ mental lexicon. Thirdly, L1 transfer is stronger at the lexical level than at the conceptual level for English idiom production. In other words, the concrete lexical units related to the L1 (Persian language here) and L2 (English language here) make stronger links between the two mental lexicons of the Iranian EFL learners inducing a faster production of the English idioms compared to the abstract shared figurative meaning. The overall findings of this study may provide not only a better understanding of the cognitive processes involved in idiom representation in EFL learners’ mental lexicon, but also a better view of idiom production and factors influencing it in EFL learning and acquisition.